Note on $p_1$-Lindelof spaces which are not contra second countable spaces in bitopology - Santanu Acharjee; Kyriakos Papadopoulos; Binod Chandra Tripathy (Boletim da Sociedade Paranaense de Matemática, 2018)
In this article we show that a contra second countable bitopological space is a $p_1$-Lindelof space, but the converse is not true in general. We provide suitable example with the help of concepts of nest and interlocking from LOTS. The relation between pairwise regular spaces and $p_1$-normal spaces is studied. At the end, we propose some open questions which may enrich various concepts related to Lindelofness in a bitopological space and other areas of mathematical ideas.